Advanced Optical Technologies (De Gruyter, 2012)
Advanced Optical Technologies is a strictly peer-reviewed scientific journal. The major aim of Advanced Optical Technologies is to publish recent progress in the fields of optical design, optical engineering, and optical manufacturing. Advanced Optical Technologies has a main focus on applied research and addresses scientists as well as experts in industrial research and development.